Canciones populares para niñas de la Sección Femenina de la Falange. Estudio de un cuaderno manuscrito de 1953 - Allué Villanueva, Consuelo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2016)
In this article, on the one hand, we offer the complete interview with Maria Cruz Villanueva, collector of a manuscript notebook –Songs– in 1953, during a summer camp organized in Poblet by the Feminine Section (which has already been included in the Archives of the Intangible Heritage of Navarre). Besides, analysing Maria Cruz’s life experiences at that time, we try to relate the information offered by her with the aims and practices of the Feminine Section of the Spanish Phalanx in its first decades of existence, more specifically the ones linked to the use of popular song.
Keywords: Song book; manuscript notebook; femenine section of the spanish phalanx; women’s education